2008
DOI: 10.2193/2007-138
|View full text |Cite
|
Sign up to set email alerts
|

Fox Squirrel Survival in Urban and Rural Environments

Abstract: A number of studies on mammalian species that have adapted to urban areas suggest survival may be higher for urban populations than rural populations. We examined differences in fatalities between an urban and rural population of fox squirrels (Sciurus niger). We radiocollared (n = 50 rural, n = 78 urban) fox squirrels during approximately 2 years. We found monthly survival of rural fox squirrels (Ŝ = 0.936) was lower than urban fox squirrels (Ŝ = 0.976) over the same 12‐month period. Nonetheless, when compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 14 publications
1
42
0
Order By: Relevance
“…Perhaps owing to the difficulty in studying small populations, few studies have documented lower survival rates for species that are negatively associated with urbanization (but see Price et al 2011). In contrast, several studies provide evidence that elevated survival rates in cities (e.g., Gosselink et al 2007;McCleery et al 2008;Lehrer et al 2012) promote high densities of species, as with raccoons (Prange et al 2003), fox squirrels (McCleery et al 2008), eastern long-necked turtles (Chelodina longicollis; Rees et al 2009), and many birds (e.g., Canada geese (Branta canadensis; Balkcom 2010); northern mockingbirds (Mimus polyglottos; Stracey and Robinson 2012), peregrine falcons (Falco peregrines anatum; Kauffman et al 2003), and great tits (Parus major; Horak and Lebreton 1998)). On the other hand, a review of carnivores showed equivocal comparisons of survival rates between urban and rural populations, with some species exhibiting greater survival with urbanization (i.e., kit foxes (Vulpes macrotis), raccoons, coyotes, stone marten (Martes foina)) and others with no change or negative trends (i.e., striped skunks, red foxes, bobcats, mountain lions (Puma concolor; Iossa et al 2010)).…”
Section: Survivalmentioning
confidence: 98%
“…Perhaps owing to the difficulty in studying small populations, few studies have documented lower survival rates for species that are negatively associated with urbanization (but see Price et al 2011). In contrast, several studies provide evidence that elevated survival rates in cities (e.g., Gosselink et al 2007;McCleery et al 2008;Lehrer et al 2012) promote high densities of species, as with raccoons (Prange et al 2003), fox squirrels (McCleery et al 2008), eastern long-necked turtles (Chelodina longicollis; Rees et al 2009), and many birds (e.g., Canada geese (Branta canadensis; Balkcom 2010); northern mockingbirds (Mimus polyglottos; Stracey and Robinson 2012), peregrine falcons (Falco peregrines anatum; Kauffman et al 2003), and great tits (Parus major; Horak and Lebreton 1998)). On the other hand, a review of carnivores showed equivocal comparisons of survival rates between urban and rural populations, with some species exhibiting greater survival with urbanization (i.e., kit foxes (Vulpes macrotis), raccoons, coyotes, stone marten (Martes foina)) and others with no change or negative trends (i.e., striped skunks, red foxes, bobcats, mountain lions (Puma concolor; Iossa et al 2010)).…”
Section: Survivalmentioning
confidence: 98%
“…For example, urban areas may support > 300 raccoons per square kilometer compared to 20/km 2 in rural sites (Lotze and Anderson 1979;Riley et al 1998), with similar trends noted for gray squirrels (Parker and Nilon 2008) and many other species. A bottom-up view of urban resource exploitation in tandem with the loss of large carnivores in cities has been used to explain the highly skewed dominancediversity relationships typically seen in urban areas (McCleery et al 2008). Indeed, some predation-risk assessments of ground-feeding birds have concluded that they perceive less risk in urban than in rural environments, presumably due to a lack of urban predators cf.…”
Section: Do Urban Wildlife Communities Follow the Same Principles As mentioning
confidence: 99%
“…Another approach is the direct monitoring of prey mortality. Studies on post-fledging and adult mortality are uncommon, because population censuses and capture-recapture methods (Chiron and Julliard, 2007;Brown and Graham, 2015) might estimate survival inaccurately, or because tracing individual prey animals (e.g., by radio-telemetry; McCleery et al, 2008;Ausprey and Rodewald, 2011;Balogh et al, 2011;Shipley et al, 2013) is often costly and based on small sample sizes. Bird nests, in contrast, are immobile, easy to monitor, and are often preyed upon by various predator species.…”
Section: Introductionmentioning
confidence: 99%